Between the conquests and the court: a critical analysis of the Kitāb Futūḥ al-Buldān of al-Balādhurī - Lynch, RJ (2016)
When considering the available sources for Islamic history between the seventh and eighth centuries CE, there are few which have greater importance than al-Balādhurī’s (d. ca. 892 CE/279 AH) Kitāb Futūḥ al-buldān (The Book of the Conquest of Lands). While the text and its author are recognized for their importance as a historical source for the early Islamic period, there has previously been no in-depth study of either. This dissertation works to correct these gaps in knowledge of the author and his text by investigating the construction, form, content, and early reception history of al-Balādhurī’s book.